Transesterification of vegetables oil in subcritical methanol conditions - Pardal, Ana Cristina (2011)
In this study, transesterification of rapeseed oil using subcritical methanol and potassium hydroxide as catalyst was studied. The variables affecting the methyl ester yield during the transesterification reaction, such as the catalyst content, reaction temperature, reaction time and the molar ratio of alcohol to oil, were investigated. The results are compared to the obtained using cosolvents. The evolution of the process was followed by gas chromatography, determining the concentration of the methyl esters. The biodiesel was characterized by its density, viscosity, saponification value, iodine value, acidity index and water content, according to ISO norms. High methyl ester yield and fast reaction rate could be obtained even if the reaction pressure was relatively low, which is quite favourable to the production of biodiesel in industry.